Opportunities and challenges for DAC members in ‘adapting to context’ - Sharp, Samuel; Wild, Leni (2021)
Key Messages New principles for OECD DAC members on ‘Managing for Sustainable Development Results’ emphasise tailoring result management approaches to different contexts; balancing internal compliance with empowerment at ground level; and adapting implementation in the pursuit of long-term outcomes. However development organisations face numerous challenges in aligning with these principles in practice. Reporting and evidence collection processes do not consistently encourage adaptive practice, reflecting their orientation towards accountability over learning. Context analysis is common during programme design, but used less on an ongoing basis. Popular tools –such as logical frameworks and theories of change - are often intepreted in linear ways, not as ‘living documents’ that react and change over time. Organisations need to meaningfully empower staff to work adaptively, including examining incentives and cultures that can make staff more comfortable with traditional results management. Even when senior leadership is supportive of adaptive ways of working, they can lack a clear understanding of the resourcing required and appropriate governance and management processes. Development organisations and their partners have attempted to address these challenges through the use of different monitoring and evaluation tools and methods, changes to reporting frameworks and templates, and initiatives to create positive incentives and motivate staff, leadership and partners at different levels.
Keywords: _tablet

Glossary of Key Terms in Evaluation and Results Based Management - OECD (OECD, 2009)

Evaluation of development programmes - OECD - OECD (2019)
Data & research on evaluation of development programmes inc. paris declaration, budget support, multilateral effectiveness, impact evaluation, joint evaluations, governance, aid for trade

Quality standards for development evaluation - OECD; Development Assistance Committee (OECD, 2010)
Based on a broad international consultative process, the DAC Quality Standards for Development Evaluation are a reference guide to good practice in development evaluation. With a view to improving the quality of evaluation processes and products, and facilitating collaboration, this reference guide lays out standards for each phase of a typical evaluation process: from defining purpose, to planning, designing, implementing, reporting, and learning from and using evaluation results.

Applying Evaluation Criteria Thoughtfully - OECD (OECD, 2021)
Relevance, coherence, effectiveness, efficiency, impact, and sustainability are widely used evaluation criteria, particularly in international development co-operation. They help to determine the merit or worth of various interventions, such as strategies, policies, programmes or projects. This guidance aims to help evaluators and others to better understand those criteria, and improve their use. It starts by describing what they are, and how they are meant to be used. Then the definitions and concepts underpinning each criterion are explained. Finally, examples provide the reader with concrete ideas for using them. The criteria were originally laid out in the early 2000s by the Network on Development Evaluation (EvalNet) of the OECD Development Assistance Committee (DAC). Although they have been widely used in evaluation, and beyond, this document is the first to comprehensively explore the concepts in detail, explain their intended use and offer practical guidance. It captures current thinking and best practice in evaluation, drawing on the inputs of internationally renowned evaluation experts from EvalNet and beyond.